Respuesta del cultivo de zanahoria blanca (Arracacia Xanthorrhiza) a la aplicación de tres láminas de riego en las terrazas de banco del campus Salache-Cotopaxi, 2023. - Tenorio Chicaiza, Omar Wladimir (2023)
The present research project was conducted on the No. five terrace of the Salache campus, Latacunga canton, Cotopaxi province in the October 2022 - February 2023 period. The main objective was to evaluate the response of the white carrot crop (Arracacia xanthorrhiza) to the application of three sheets. The treatments consisted of applying one sheet at 100% of crop evapotranspiration (control) and two deficit sheets; at 90% and 80% of crop evapotranspiration (ET), under high-frequency localized irrigation in the white carrot crop. The experimental design was a randomized complete block design with three repetitions. The results allowed identifying that the initial phase and vegetative development are affected by water deficit, evidencing its effect on the budding variables percentage, plant height, number of leaves and failure percentage. However, there is no evidence of its influence on the value of cover and stem diameter. The analysis of variance for height at 57 days showed that there was significance for the plant height variable, with two height groups. For the mortality variable percentage, there was a high significance, with three mortality groups. For the failure variable percentage, there was high significance, with three failure groups. For the leaf number variable, there was high significance, with two groups, the No. 1 treatment was better at 100 ET. However, for the variable of stem diameter and ground cover value, there was no significance, with only one group.